Epistemic emotions and self-trust - Anna Bortolan (Phenomenology and the Cognitive Sciences, 2024)
Epistemic emotions – namely affective phenomena like curiosity, certainty, and doubt – have been claimed to play a key role in epistemic evaluation and motivation, and, relatedly, to be an integral aspect of the epistemic virtues. In this paper I argue that the experience of epistemic emotions is extensively shaped by self-trust. More specifically, I claim that the set of epistemic emotions that we can undergo, and how these unfold over time, is modulated by the level of trust in one’s abilities as a knower. I do so by drawing on research on epistemic injustice, as well as through the exploration of some features of obsessive-compulsive disorder (OCD) and depression. I then argue that the connection between epistemic emotions and self-trust can be best accounted for by conceiving of self-trust, through the framework of philosophical phenomenology, as an affective background orientation which has a structuring role in our cognitive and affective experience.